237 The WHAT-ME Study: Relationships between work practices and urinary metal concentrations among women working in non-traditional trades. (11th October 2013) - Arrandale, H; Manning,; Beach,; Cherry, M
Abstract : Objectives: The WHAT-ME cohort is a prospective study of reproductive health among Canadian women in non-traditional trades. The goal of this sub-study was to investigate associations between the exposure questionnaire and urinary metal concentrations. Methods: Women registered in welding, boilermaking, steam fitting/pipefitting ('welders') or electrical trade apprenticeships since 2005 were invited to join the cohort. Participants in the Alberta sub-study mailed-in a urine sample at 6 months. Correlations between urinary metals (by ICP MS) were investigated and principal components extracted. Relationships between individual metals, component scores and work practices (from exposure questionnaires at 6 months) were investigated. Results: 183 urine samples were collected. Analysis was limited to 108 subjects (57 welders, 51 electricians) who had completed trade-specific work since enrolment. Smokers (38%) had significantly higher urinary concentrations of cadmium, cobalt and lead. Metal concentrations were more strongly correlated in welders than electricians. In welders, the first principal component explained 46% of the variability in metal concentrations but for electricians only 23%. Geometric mean of each of the 12 metals measured was higher for welders than electricians: only chromium reached significance (0.51 vs. 0.16 ug/g-creatinine, p<0.001). Among welders, tungsten inert gas (TIG) welders tended to have lower metal concentrations while those doing manual metal arc welding had significantly higher zinc concentrations (p < 0.05). Preliminary analyses of work practices suggest that both personal protective equipment and local exhaust ventilation were related to urinary metal concentrations; supplementary analyses will also include data on consumables and base metals. Conclusions: Urinary metal concentrations tended to be higher and more strongly correlated among welders compared with electricians. Welding tasks, materials and controls associated with urinary metal concentrations will guide strategies for exposure reduction in the welding trade.